2015
DOI: 10.1007/s10959-015-0602-3
|View full text |Cite
|
Sign up to set email alerts
|

Semicircle Law for a Matrix Ensemble with Dependent Entries

Abstract: We study ensembles of random symmetric matrices whose entries exhibit certain correlations. Examples are distributions of Curie-Weiss-type. We provide a criterion on the correlations ensuring the validity of Wigner's semicircle law for the eigenvalue distribution measure. In case of CurieWeiss distributions this criterion applies above the critical temperature (i. e. β < 1). We also investigate the largest eigenvalue of certain ensembles of Curie-Weiss type and find a transition in its behavior at the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…If it does not decay to 0 (and have the same sign) the semicircle law cannot be the limit of the ESD. This is good agreement with results on exchangeable processes analysed in Friesen and Löwe (2013a) and Hochstättler et al (2016).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…If it does not decay to 0 (and have the same sign) the semicircle law cannot be the limit of the ESD. This is good agreement with results on exchangeable processes analysed in Friesen and Löwe (2013a) and Hochstättler et al (2016).…”
supporting
confidence: 92%
“…Similar attempts have been made in Schenker and Schulz-Baldes (2005), where a limited number of correlated entries are admitted, Götze and Tikhomirov (2006), where a martingale structure of the entries is imposed, Friesen and Löwe (2013b), where the diagonals of the (symmetric) matrices were filled with independent Markov chains or in Löwe and Schubert (2016), where the upper triangular part of the matrix is filled with a one-dimensional Markov chain. On the other hand, Friesen and Löwe (2013a) and Hochstättler et al (2016) study matrices where either the diagonals or the entire matrix is built of exchangeable random variables. In particular, in Friesen and Löwe (2013a) it was shown that there is a phase transition: If the correlation of the exchangeable random variables go to 0, the limit of the ESD is the semi-circle law, while otherwise it can be described in terms of a free convolution of the semi-circle law with a limiting law obtained in Bryc et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The following result is proved in [13]. The purpose of the present paper is to extend this result to subcritical temperatures β > 1.…”
Section: Observe That Pmentioning
confidence: 66%
“…Observe that the definition in [13] is even more general than Definition 1. It also allows to replace F β by more general functions F (cf.…”
Section: Observe That Pmentioning
confidence: 99%
See 1 more Smart Citation